Ethical leadership practices and trust among public school leaders in Malaysia / Sharmini Siva Vikaraman ... [et al.] - Vikaraman, Sharmini Siva; Mansor, Azlin Norhaini; Mohd Nor, Mohamed Yusoff; Alias, Bity Salwana; Gurusamy, Vasanthan (Universiti Teknologi MARA, 2021)
Integrating values in managing a school is crucial to balance the role of school leaders as leaders and managers under one roof. This study highlights the practice of ethical leadership (branch of value-based leadership) based on seven dimensions. Using a mixed method (QUAN-qual) approach, this study i) identifies the level of principal's ethical leadership practices and trust in leader as perceived by primary and secondary school teachers of Malaysia, ii) explores the relationship between both variables and classifies accordingly the sub constructs of ethical leadership practices that significantly contribute to developing trust in their leaders, iii) ascertain the understanding and practices of ethical leadership style among the principals as perceived by the principals themselves. The quantitative data were collected via Ethical Leadership at Workplace (ELW) and Trust in Leader (TL) questionnaire. A total of 438 public school teachers nationwide responded to the questionnaire. Data were analyzed using descriptive and inferential statistical method. The findings show that principals throughout the country practiced high ethical leadership. The level of teacher's trust in principals was also high. The inference analysis found very strong significant relationship between ethical leadership and teachers' trust on their principals. A semi-structured interview with three school principals was conducted to collect the qualitative data revealed that the Malaysian principals lacked the understanding of ethical leadership style, nevertheless practiced several dimensions of ethical leadership in their school administration. The study suggests ethical leadership to be integrated into current school leadership practices to further understand its impact.